Control of the Normal and Pathological Development of Neural Stem and Progenitor Cells by the PC3/Tis21/Btg2 and Btg1 Genes. Issue 12 (24th August 2015) - Micheli, Laura; Ceccarelli, Manuela; Farioli‐Vecchioli, Stefano; Tirone, Felice
<x xml:space="preserve">Abstract</x> The PC3/Tis21/Btg2 and Btg1 genes are transcriptional cofactors belonging to the Btg/Tob family, which regulate the development of several cell types, including neural precursors. We summarize here the actions of these genes on neural precursors in the adult neurogenic niches and the cognitive defects associated when their expression is altered. We consider also recent findings implicating them in neural and non‐neural tumors, since common developmental mechanisms are involved. PC3/Tis21 is required for the regulation of the maturation of stem and progenitor cells in the adult dentate gyrus and subventricular zone (SVZ), by controlling both their exit from the cell cycle and the ensuing terminal differentiation. Such actions are effected by regulating the expression of several genes, including cyclin D1, BMP4, Id3. In cerebellar precursors, however, PC3/Tis21 regulates chiefly their migration rather than proliferation or differentiation, with important implications for the onset of medulloblastoma, the cerebellar tumor. In fact PC3/Tis21 is a medulloblastoma‐suppressor, as its overexpression in cerebellar precursors inhibits this tumor; PC3/Tis21 shows anti‐tumor activity also in non‐neural tumors. Btg1 presents a different functional profile, as it controls proliferation in adult stem/progenitor cells of dentate gyrus and SVZ, where is required to maintain their self‐renewal and quiescence, but is apparently devoid of a direct control of their terminal differentiation or migration. Notably, physical exercise in Btg1‐null mice rescues the loss of proliferative capability occurring in older stem cells. Both genes could be further investigated as therapeutical targets, namely, Btg1 in the process of aging and PC3/Tis21 as a tumor‐suppressor. J. Cell. Physiol. 230: 2881–2890, 2015. © 2015 Wiley Periodicals, Inc.